Genetic Diversity of Butterfly Pea (Clitoria ternatea) from Indonesia Based on Flower and Yield Component Traits in Two Land Conditions - Trixie A. Ulimaz; Debby Ustari; Virda Aziza; Tarkus Suganda; Vergel Concibido; Jutti Levita; Agung Karuniawan (Jurnal AgroBiogen, 2020)
Genetic diversity among the butterfly pea genotypes is important information to support breeding program of this underutilized crop. The important characters to be targeted in the breeding program of this crop included yield and yield components of flowers that are strongly affected by the environment and have not been previously reported. This study aimed to determine the genetic diversity of butterfly pea (Clitoria ternatea L.) from Indonesia tested in two land conditions, namely dryland and former paddy fields, based on flower character and yield component traits. The results showed that butterfly pea accessions were divided into two main clusters with dissimilarity coefficient of 0.01–3.99 indicating wide genetic diversity across  accessions. The Mantel correlation showed that the genetic distance among accessions studied were not significantly correlated (r = 0.044, P = 0.8709). Based on principal component analysis (PCA), the eigenvalue ranged from 1.69 to 3.34 with a cumulative contribution of 72.64%. The traits that influenced genetic diversity in this study were flower length, weight of one fresh flower, total weight of pods, and weight of 100 seeds. The results of this study should be useful to support future butterfly pea breeding program.